DEVELOPMENT OF INFORMATIONAL RESOURCES PERTAINING TO ZOONOTIC DISEASES FOR KANSAS MEDICAL PROFESSIONALS - Van Nest, Kortnee (My University, 2024)
As zoonotic diseases represent the majority of all emerging diseases, there is an increasing risk to public health. Zoonotic diseases infect both animals and humans and thus require both veterinary and human medical professional intervention. However, there may be a lack of cooperation between the two professions. Moreover, these medical professionals must be able to provide critical information about the transmission of zoonotic disease for patients and/or animal owners. Although these topics are critical for facing zoonotic disease, practitioners may not have easy-to-access resources to reference when faced with zoonoses. To address these concerns, I worked with the National Agricultural Biosecurity Center to create information handouts. By forming a multidisciplinary team, we identified which zoonoses are of highest concern to Kansas and what information for each disease was the most important. This information was then used to create two sets of handouts. The first set of zoonoses handouts were specifically for veterinarians and human medical professionals. The second set of handouts were tailored for veterinarians to provide to animal owners when faced with certain diseases. These handouts will provide medical professionals with the necessary information they need to address the disease as well as encourage collaboration and education efforts between professions. Through these projects, I was able to expand my knowledge of zoonotic disease and amplify my skills of working on multidisciplinary teams.
Keywords: Zoonosis; Infectious Disease; One Health; Veterinary Medicine